2018
DOI: 10.1111/jgs.15236
|View full text |Cite
|
Sign up to set email alerts
|

Syncope, Hypotension, and Falls in the Treatment of Hypertension: Results from the Randomized Clinical Systolic Blood Pressure Intervention Trial

Abstract: Participants randomized to intensive SBP control had greater risk of hypotension and possibly syncope, but not falls. The greater risk of developing these events associated with intensive treatment did not vary according to age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 19 publications
5
64
0
4
Order By: Relevance
“…Finucane et al also found a 40% increased risk of falls at 2 years of follow‐up in people with orthostatic hypotension in a population‐based prospective study in Irish adults . The SPRINT study also supported this finding, as did smaller and cross‐sectional studies, although one moderately large prospective study did not …”
Section: Discussionmentioning
confidence: 85%
“…Finucane et al also found a 40% increased risk of falls at 2 years of follow‐up in people with orthostatic hypotension in a population‐based prospective study in Irish adults . The SPRINT study also supported this finding, as did smaller and cross‐sectional studies, although one moderately large prospective study did not …”
Section: Discussionmentioning
confidence: 85%
“…For this analysis, the final date of follow-up was July 22, 2018. Adverse events during the intervention phase of the trial have been publishedpreviously 13,14,28 ; additional adverse event data were not collected during the extended follow-up visits.…”
Section: Methodsmentioning
confidence: 99%
“…In both SPRINT and the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial, intensive therapy was not associated with meaningful changes in health‐related quality of life . As with other clinical trials, the lower blood pressure target in SPRINT was unaccompanied by increases in injurious falls …”
Section: Discussionmentioning
confidence: 95%
“…FSE was measured at baseline, 6 months, 1 year, and annually thereafter until study end. Information on the occurrence of injurious falls was collected quarterly and in the reporting of serious adverse events …”
Section: Methodsmentioning
confidence: 99%